1985
DOI: 10.1002/1097-0142(19850801)56:3<703::aid-cncr2820560344>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of stomach cancer in a coal mining region of Pennsylvania

Abstract: Historically coal mining populations have been reported to have elevated stomach cancer incidence rates. To identify which factors might be associated with cases who reside in these high risk areas, and specifically if particulate exposures from coal mining and coal utilization are associated with risk, a mining area of western Pennsylvania was defined for a retrospective case-control study. One hundred seventy-eight resident cases, identified from certificates of death, were compared to three controls: digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 14 publications
1
8
1
Order By: Relevance
“…The Third National Cancer Survey of the United States (37) and studies elsewhere reported a non-significant risk of stomach cancer with smokeless tobacco use (31,38,39). Our study revealed significant elevated risk among the chewers of tobacco only (smokeless tobacco) and tuibur users than the nonusers, which supported the findings of toxicity of tuibur (8).…”
Section: Discussionsupporting
confidence: 87%
“…The Third National Cancer Survey of the United States (37) and studies elsewhere reported a non-significant risk of stomach cancer with smokeless tobacco use (31,38,39). Our study revealed significant elevated risk among the chewers of tobacco only (smokeless tobacco) and tuibur users than the nonusers, which supported the findings of toxicity of tuibur (8).…”
Section: Discussionsupporting
confidence: 87%
“…The remaining 34 studies were separated into two main categories: A) 27 studies of coal mining as an occupational risk factor for cancer [19]–[45], and B) 7 ecological/cross-sectional studies of coal mining and associated cancer risk in the surrounding population [46]–[52]. The occupation studies may be further classified as: A1) those that examined cohorts of coal miners (standardized incidence/mortality ratios calculated; SIR/SMR; relative risks (RR)) [19]–[28], and A2) those examining coal mining as a risk factor in case-control analysis (odds ratios (OR) calculated) [29]–[45]. While categories A1 and A2 both explicitly examine coal mining and associated cancer risk, category A1 does so by specifically selecting coal miners for comparison to others (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…For a further 38 studies [36,38-40,42,44-46,49,51,53,54,56,57,59,60,63,64,67,70-73,75,78,80-82,84-86,92,95,96,98,100,103,110] the results available for ST are for the whole population, with no adjustment for smoking (category B). In 14 studies [43,47,48,66,69,74,76,83,87,88,99,101,111,112] the only relevant smoking-adjusted results reported are for never smokers (category C).…”
Section: Resultsmentioning
confidence: 99%